Socio-economic determinants of fruits and vegetable consumption: insights from a survey in Delhi - Gupta, Nisha; Bhattacharjee, Mahua; Saha, Anindita Roy (Journal of Postharvest Technology, 2022)
India has experienced a structural transformation in its food consumption with a drastic shift from staples to high value agricultural product food items like fruits, vegetables, milk, meat, fish and eggs. However consumption levels of these food items are far below the nutritional guideline which leads to an increasing burden of non-communicable diseases especially in the fast paced urban sector. This paper attempts to study the consumption pattern of fruits and vegetables in Delhi along with the enablers of their consumption. Data has been collected using a structured questionnaire on 304 urban samples from different districts of Delhi. Using descriptive statistics and non-parametric techniques like Kruskal Wallis test it has been found that gender, education and monthly income of a household among the socio demographic factors and health perception of the consumer, physical attributes of the food item along with the ease of availability of the quality food items are the main drivers of the FandV consumption. Identification of the main drivers involved in consumption, and the overall perception of the consumers towards these food items, may contribute to a better definition of health promotion initiatives aiming to improve nutritional intake across the different sections of the society.